Call the midwife. Season eight [videorecording (DVD)] - Macartney, Syd, 1954-; Saxon, Kate; Agutter, Jenny; Bassett, Linda; George, Helen, 1984- (BBC, 2018)
Follows a group of midwives in the East End of London in the early 1960s.